Evaluation of oral keratinocyte progenitor and T-lymphocite cells response during early healing after augmentation of keratinized gingiva with a 3D collagen matrix - a pilot study. Issue 1 (December 2017) - Rusu, Darian; Calenic, Bogdan; Greabu, Maria; Kralev, Alexander; Boariu, Marius; Bojin, Florina; Anghel, Simona; Paunescu, Virgil; Vela, Octavia; Calniceanu, Horia; Stratul, Stefan-Ioan
Abstract Background The aim of the present study is to analyze the behavior of selected populations of oral keratinocytes and T-lymphocytes, responsible for re-constructing and maintaining the oral epithelial tissue architecture, following augmentation of the keratinized oral mucosa using a 3D-collagen matrix. Methods Different groups of oral keratinocytes were isolated from biopsies harvested from 3 patients before the surgical procedure, as well as 7 and 14 days after the augmentation procedure. T-lymphocytes were isolated from peripheral blood at same timepoints. Keratinocytes were characterized for stem and differentiation markers, such as p63, cytokeratin 10 and 14, and in vitro parameters, such as cell viability, cell size and colony-forming efficiency. T-lymphocytes were analyzed for viability and the expression of various cluster of differentiation markers. The methods included magnetic separation of cell populations, immunofluorescence, flow cytometry, and histology of oral biopsies. Results Both at 7 and 14 days, the majority of cells that repopulate the matrix were actively proliferating/progenitor oral keratinocytes with the phenotype integrin alfa6beta4 + CD71+. These cells display in vitro characteristics similar to the progenitor cells analyzed before the matrix placement. T-lymphocytes expressed CD8 and CD69 markers, while CD25 was absent. Conclusion The study shows that two weeks after the collagen membrane placement, the healing process appeared to be histologically complete, with no abnormal immune response induced by the matrix, however, with a higher than usual content of active proliferating cells, the majority of keratinocytes being characterized as transit amplifying cells.